Utility of total lymphocyte count as a surrogate marker for CD4 counts in HIV-1 infected children in Kenya - Githinji, Nyawira (BioMed Central, 2011)
BACKGROUND: In resource-limited settings, such as Kenya, access to CD4 testing is limited. Therefore, evaluation of less expensive laboratory diagnostics is urgently needed to diagnose immuno-suppression in children. OBJECTIVES: To evaluate utility of total lymphocyte count (TLC) as surrogate marker for CD4 count in HIV-infected children. METHODS: This was a hospital based retrospective study conducted in three HIV clinics in Kisumu and Nairobi in Kenya. TLC, CD4 count and CD4 percent data were abstracted from hospital records of 487 antiretroviral-naïve HIV-infected children aged 1 month - 12 years. RESULTS: TLC and CD4 count were positively correlated (r = 0.66, p < 0.001) with highest correlation seen in children with severe immuno-suppression (r = 0.72, p < 0.001) and children >59 months of age (r = 0.68, p < 0.001). Children were considered to have severe immuno-suppression if they met the following WHO set CD4 count thresholds: age below 12 months (CD4 counts < 1500 cells/mm(3)), age 12-35 months (CD4 count < 750 cells/mm3), age 36-59 months (CD4 count < 350 cells/mm(3), and age above 59 months (CD4 count < 200 cells/mm(3)). WHO recommended TLC threshold values for severe immuno-suppression of 4000, 3000, 2500 and 2000 cells/mm(3 )for age categories <12, 12-35, 36-59 and >59 months had low sensitivity of 25%, 23%, 33% and 62% respectively in predicting severe immuno-suppression using CD4 count as gold standard. Raising TLC thresholds to 7000, 6000, 4500 and 3000 cells/mm(3 )for each of the stated age categories increased sensitivity to 71%, 64%, 56% and 86%, with positive predictive values of 85%, 61%, 37%, 68% respectively but reduced specificity to 73%, 62%, 54% and 68% with negative predictive values of 54%, 65%, 71% and 87% respectively. CONCLUSION: TLC is positively correlated with absolute CD4 count in children but current WHO age-specific thresholds had low sensitivity to identify severely immunosuppressed Kenyan children. Sensitivity and therefore utility of TLC to identify immuno-suppressed children may be improved by raising the TLC cut off levels across the various age categories.